Reduced metabolism in the hypothalamus of the anorectic anx/anx mouse. Issue 1 (April 2017) - Bergström, Ulrika; Lindfors, Charlotte; Svedberg, Marie; Johansen, Jeanette E; Häggkvist, Jenny; Schalling, Martin; Wibom, Rolf; Katz, Abram; Nilsson, Ida A K
Abstract : The anorectic anx/anx mouse exhibits a mitochondrial complex I dysfunction that is related to aberrant expression of hypothalamic neuropeptides and transmitters regulating food intake. Hypothalamic activity, i.e. neuronal firing and transmitter release, is dependent on glucose utilization and energy metabolism. To better understand the role of hypothalamic activity in anorexia, we assessed carbohydrate and high-energy phosphate metabolism, in vivo and in vitro, in the anx/anx hypothalamus. In the fasted state, hypothalamic glucose uptake in the anx/anx mouse was reduced by 50% of that seen in wild-type (wt) mice ( P < 0.05). Under basal conditions, anx/anx hypothalamus ATP and glucose 6-P contents were similar to those in wt hypothalamus, whereas phosphocreatine was elevated ( 2-fold; P < 0.001) and lactate was reduced ( 35%; P < 0.001). The anx/anx hypothalamus had elevated total AMPK ( 25%; P < 0.05) and GLUT4 ( 60%; P < 0.01) protein contents, whereas GLUT1 and GLUT3 were similar to that of wt hypothalamus. Interestingly, the activation state of AMPK (ratio of phosphorylated AMPK/total AMPK) was significantly decreased in hypothalamus of the anx/anx mouse ( 60% of that in wt; P < 0.05). Finally, during metabolic stress (ischemia), accumulation of lactate (measure of glycolysis) and IMP and AMP (breakdown products of ATP) were 50% lower in anx/anx vs wt hypothalamus. These data demonstrate that carbohydrate and high-energy phosphate utilization in the anx/anx hypothalamus are diminished under basal and stress conditions. The decrease in hypothalamic metabolism may contribute to the anorectic behavior of the anx/anx mouse, i.e. its inability to regulate food intake in accordance with energy status.